2016
DOI: 10.1097/md.0000000000005236
|View full text |Cite
|
Sign up to set email alerts
|

Implementing web-based ping-pong-type e-communication to enhance staff satisfaction, multidisciplinary cooperation, and clinical effectiveness

Abstract: Background:Frequent multidisciplinary communication is essential in conducting daily radiotherapy (RT) practice. However, traditional oral or paper-based communication has limitations. E-communication has been suggested, but its effects are still not well demarcated in the field of radiation oncology.Objects:In our web-based integrated information platform, we constructed a ping-pong-type e-communication function to transfer specific notations among multidisciplinary RT staffs. The purpose was to test whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Technology, such as telecommunication, facilitates teamwork as it creates the opportunity to involve and interact with professionals from a distance [271][272][273]. Technology also creates opportunities to exchange information through information platforms [276,277]. Most studies found positive results for teamwork.…”
Section: Facilitating Toolsmentioning
confidence: 99%
“…Technology, such as telecommunication, facilitates teamwork as it creates the opportunity to involve and interact with professionals from a distance [271][272][273]. Technology also creates opportunities to exchange information through information platforms [276,277]. Most studies found positive results for teamwork.…”
Section: Facilitating Toolsmentioning
confidence: 99%
“…A neurosurgeon and two radiation oncologists doubly reviewed all data. Patients' medical profiles and radiation parameters were retrieved from hardcopy medical charts, the Hospital Information System, and our in-house RT database, the Integrated Radiotherapy Oncology Information Platform (26,27). Documented baseline data included patient characteristics, tumor-specific profiles, and radiation parameters (e.g., irradiation dosimetry, cochlear dose, and tumor volume).…”
Section: Subjects and Populationsmentioning
confidence: 99%
“…After salvage microsurgery, the patient's symptoms improved gradually, free from medications for fourteen years. Left 25 [50] 13 [26] 12 [24] Symptoms for SRS, n [%] 0.75 Tinnitus 23 [46] 16 [32] 7 [14] Dizziness 24 [48] 11 [22] 13 [26] Hearing impairment 22 [44] 10 [20] 12 [24] Imbalance 8 [16] 5 [10] 3 [6] Trigeminal neuralgia 4…”
Section: Tcrmentioning
confidence: 99%
“…Informed written consent was waived by the IRB because the study was a retrospective data analysis. We retrospectively retrieved and analyzed data from medical records and our prospective departmental database, i.e., our Integrated RT Oncology Information Platform [ 16 17 ].…”
Section: Aterials and M Ethodsmentioning
confidence: 99%